Reclaiming Voice in AI-Mediated Personal Statements: A Critical AI Literacy Framework for L2 Writers - Sulaiman, Thuraya (2025)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Thuraya Sulaiman entitled, “Reclaiming Voice in AI-Mediated Personal Statements: A Critical AI Literacy Framework for L2 Writers”, submitted in November 2025. Thesis advisor is Dr. Neslihan Bilikozen. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).